Positive allosteric modulators of metabotropic glutamate 2 receptors in schizophrenia treatment. Issue 8 (August 2015) - Ellaithy, Amr; Younkin, Jason; González-Maeso, Javier; Logothetis, Diomedes E.
Highlights mGlu2R activation is a potential therapeutic strategy for schizophrenia. Unlike orthosteric agonists, positive allosteric modulators have a unique ability to fine-tune physiological responses. Chronic atypical antipsychotic therapy may reduce the efficacy of mGlu2R antipsychotics.